A Study On The Effect Of Spur Dike On The Formation Of Sand Bar In A Rectangular Channel - Hamidi, Muhammad Azfar (Universiti Sains Malaysia, 2022)
Spur dike is one of the various technologies utilized in river rehabilitation. Spur dike provides many advantages such as promoting aquatic habitat, improving channel for navigation and protecting the stream banks. Water depth can be raised by constructing perpendicular spur dike. Flow velocity also is low behind the spur dike. This study serves to evaluate the effect of a spur dike on the formation of sand bar in a straight rectangular channel. The performance of the spur dike in inducing the formation of spur dike is investigated under three different spur dike angles. A three-dimensional (3D) model was built using Flow-3D to investigate the flow depth and velocity around the spur dike. Based on the velocity distribution, the influence of spur dike angle on the formation of sand bar was explained. A scalar concentration is used to represent the suspended sediment as in the simulation, and the formation of sand bar is represented by the scalar concentration. From the numerical results, it was found that the 90 degree angle spur dike induced larger and longer sand bar compared to the 45 degree and 135 degree angle spur dike.